2019
DOI: 10.2174/1573406415666190206232816
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene Glycol Acts as a Mechanistic Stabilizer of L-asparaginase: A Computational Probing

Abstract: Background: L-asparaginase (L-ASN) is an anti-cancer enzyme therapeutic drug that exerts cytotoxicity via inhibition of protein synthesis through depletion of L-asparagine in the tumor microenvironment. The therapeutic performance of the native drug is partial due to the associated instability, reduced half-life and immunogenic complications. Objective: In this study, we attempted the modification of recombinant L-asparaginase with PEG and an integrated computational strategy to probe the PEGylation in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Settanni et al simulated a mixture of PEG and plasma proteins such as serum albumin, transferrin, complement Cq1, and apolipoprotein A1, and calculated the local density of PEG near individual amino acids, the preferential binding coefficient of each peptide for PEG [59,60], and the conformation and thickness of PEG layer adsorbed on the protein surface [61], showing that PEG-protein interactions can be quantified by a simple model in terms of the solvent-accessible surface area exposed by each amino acid type on the protein surface, favorably compared with experimental results obtained by label-free proteomic mass spectrometry. Kurinomaru et al [62], Zaghmi et al [63], and Sindhu et al [64] found the effect of PEGylation on the structure, dynamics, and binding affinity of enzyme-therapeutic drugs such as α-amylase, glutamate dehydrogenase, and L-asparaginase, respectively. The Colina group reparameterized non-bonded potential parameters of the MARTINI CG PEG FF that was previously developed by Lee et al [25] and Rossi et al [26], which allows the accurate prediction of the interactions between PEG and proteins [65].…”
Section: Proteinsmentioning
confidence: 99%
“…Settanni et al simulated a mixture of PEG and plasma proteins such as serum albumin, transferrin, complement Cq1, and apolipoprotein A1, and calculated the local density of PEG near individual amino acids, the preferential binding coefficient of each peptide for PEG [59,60], and the conformation and thickness of PEG layer adsorbed on the protein surface [61], showing that PEG-protein interactions can be quantified by a simple model in terms of the solvent-accessible surface area exposed by each amino acid type on the protein surface, favorably compared with experimental results obtained by label-free proteomic mass spectrometry. Kurinomaru et al [62], Zaghmi et al [63], and Sindhu et al [64] found the effect of PEGylation on the structure, dynamics, and binding affinity of enzyme-therapeutic drugs such as α-amylase, glutamate dehydrogenase, and L-asparaginase, respectively. The Colina group reparameterized non-bonded potential parameters of the MARTINI CG PEG FF that was previously developed by Lee et al [25] and Rossi et al [26], which allows the accurate prediction of the interactions between PEG and proteins [65].…”
Section: Proteinsmentioning
confidence: 99%